Dynamic changes of nutrient composition throughout the entire life cycle of black soldier fly. - Xiu Liu; Xuan Chen; Hui Wang; Qinqin Yang; Kashif Ur Rehman; Wu Li; Minmin Cai; Qing Li; Lorenzo Mazza; Jibin Zhang; Ziniu Yu; Longyu Zheng (PLoS ONE)
Black soldier fly (BSF) larvae, Hermetia illucens L., develops on organic wastes, reducing ecological pollution and converting waste biomass into protein and fat rich insect biomass. BSF can replace increasingly expensive protein sources used in poultry, aquaculture and livestock compound diet formulation, such as fish meal and soybean meal, which holds the potential to alleviate future food and feed insecurity. The fate of nutritional spectra in BSF during its life cycle phases is still poorly understood. This study assessed metabolic changes in nutrition composition of BSF from egg to adult. A rapid increase of crude fat content was observed since the development of 4-14 days of larvae with its maximum level reaching 28.4% in dry mass, whereas the crude protein displayed a continuous decreasing trend in the same development phases with minimum level of 38% at larval phase (12 days) and peak level of 46.2% at early pupa stage. A sharp drop in crude fat was noticed from early prepupae to late pupae (24.2%, 8.2% respectively). However crude protein shows its maximum value being 57.6% at postmortem adult stage with 21.6% fat level. In addition, fatty acids, amino acids, minerals and vitamins composition in different development stages of BSF were presented and compared. Findings from this study could provide podium to food and feed industry for framing a strategy for specific molecular nutritional component intake into the diets of humans, aquaculture and animals. It is also indicated that BSF is a possible insect which can be applied to combating the food scarcity of countries where micronutrient deficiency is prevalent. Moreover it contributes to advance exploring for developmental and metabolic biology of this edible insect.